A RELEVÂNCIA DO DIREITO DOS ANIMAIS NA EFETIVIDADE DO DESENVOLVIMENTO SUSTENTÁVEL E DA SUSTENTABILIDADE - Mylene Priscilla de Oliveira de Souza (2022)
This study aims to analyze animal law and the historical evolution of the concepts of sustainable development and sustainability, from the international and national legislation that permeates both subjects, in order to bring them closer and highlight the relevance of animal law in the promotion of sustainable development and sustainability. For this purpose, the descriptive and exploratory, bibliographical and documentary research method was used, as well as the survey of data provided by the main research bases. In conclusion so far, it has been observed that abandoning the strictly human-centered paradigm and treating animals as subjects of rights is vital for environmental balance and human survival on Earth. Society has evolved to ensure protection, animal welfare and ethical use. However, much remains to be done to achieve a balance between human and animal rights. Therefore, the expansion and strengthening of Animal Law, through more assertive legislation and interpretations truly focused on animal protection, has the power to give voice to those who cannot express their pain or claim their own rights. Furthermore, the strengthening of this branch of Law, added to the debate around the new post-humanist paradigm that we are experiencing, consequently, implies bringing society closer to the ideals and effectiveness of sustainable development and sustainability. Keywords: Animal Rights. Sustainable development. Sustainability. Effectiveness.